A high-speed single-photon detection scheme based on frequency domain filtering. (1st August 2022) - Wu, Jin; Rong, Yue; Wan, Chenggong; Shi, Yumeng; Sun, Xingsheng; Zheng, Lixia; Sun, Weifeng
Abstract: This paper presents a high-speed integrated circuit for narrow-gated single-photon detection. Due to the parasitic capacitor that exists in the avalanche photo-diode (APD), the avalanche signal pulse triggered by the received photon is easily mixed with unavoidable spike noise arising from the gated clock. The traditional double-ended architecture extracts avalanche signals by suppressing common-mode noise. In order to overcome the shortcomings of high cost and mismatch in the traditional architecture, this paper adopts a single-ended detection architecture and deals with the problem of spike noise from the perspective of the frequency domain. According to the difference between the frequency characteristics of the spike noise and the avalanche signal, the effective separation of the two signals can be realized in the frequency domain by a low-pass filter with a specific cut-off frequency. The signal-to-noise ratio of the detection system is improved by using the subsequent amplification and discrimination circuit, so as to realize sensitive detection of the avalanche signals. The proposed circuit is implemented in 180 nm complementary metal oxide semiconductor technology and occupies an effective area of 2.6 mm 2 . The test results show that the single-ended detection system can sensitively discriminate photon signals with an emission frequency below 20 MHz when the whole circuit, including the APD, is operated at room temperature, where the minimum voltage amplitude converted from the avalanche current of the APD is around 20 mV, and the stopband attenuation of the filter at 1 GHz frequency is −58.8 dB.